The outcrop of the Menilite Beds in Kobielnik village – its geoeductional significance and an example of determining structural position based on clastic dykes - Barmuta, Maria; Barmuta, Jan; Golonka, Jan (Geotourism/Geoturystyka, 2014)
The location and most interesting geological features of the outcrop of the Menilite Beds in Kobielnik village were described in the text. However, the main subject is the problem of determining the structural position in the absence of typical indicators of the bed’s top and bottom. The proposed solution is based on the observation of clastic dykes and their structural relationship to the surrounding layers. In addition, some sedimentary structures and natural bitumen’s seepages were described.